1973
DOI: 10.1104/pp.52.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of 2,4-Dichlorophenoxyacetic Acid and 3-(p-Chlorophenyl)-1, 1-dimethylurea (Monuron) by Barley Roots

Abstract: Absorption from culture solution of the herbicides 2,4-dichlorophenoxyacetic acid (2,4-D) and 3-(p-chlorophenyl)-1, 1-dimethylurea (Monuron) by excised barley (Hordeum vulgare L.) roots was studied to determine whether absorption was due to an active or a passive mechanism. Herbicide absorption was followed at low temperature, under anaerobic conditions, and in the presence of metabolic inhibitors and compounds of structure similar to that of the herbicide. Total absorption was divided into two phases, exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…With the exception of 2,4-D (6,18), herbicides have seldom been reported to require a carrier-mediated transport system for uptake across the plasmalemma. Recent evidence from our laboratories suggested that paraquat is taken up by maize (Zea mays L. cv 3377 Pioneer) root epidermal and cortical cells via a protein-mediated system.…”
mentioning
confidence: 99%
“…With the exception of 2,4-D (6,18), herbicides have seldom been reported to require a carrier-mediated transport system for uptake across the plasmalemma. Recent evidence from our laboratories suggested that paraquat is taken up by maize (Zea mays L. cv 3377 Pioneer) root epidermal and cortical cells via a protein-mediated system.…”
mentioning
confidence: 99%
“…The Absorption in Live and Dead Tissue. The experimental approach used in this research was similar to that described by Peterson and Edgington (20) 429 Bq nmolt') were prepared in solutions of distilled water:ethanol (9:1, v/v) so that the final herbicide concentration, when 10 Ml of these solutions was added to 3.0 ml buffer, was 1.0 uM. The 14C content of the solutions was measured by taking a 50-Ml aliquot at specified time intervals (including t = 0, immediately after the herbicide was added) and assaying for 14C by LSS.…”
mentioning
confidence: 99%
“…In the case of passive physical absorption, the Q 10 value should be low, normally around 1.0 (26,33). Theoretically, a solute must be neutrally charged and lipid-soluble in order to diffuse passively across a membrane.…”
Section: Discussionmentioning
confidence: 99%
“…10/(T2ϪT1) (K 2 and K 1 represent the absorption rate at temperature T 2 and T 1 , respectively) (26). The pH dependence of uptake of p-OHBG was determined by incubation of 1 ml of protoplasts in uptake reaction mixtures containing 10 mM MES-Tris of pH 4, 5, 5.5, 6, 7, and 8.…”
Section: Methodsmentioning
confidence: 99%